Pengaruh Gaya kepemimpinan, Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan di Naturale Villa Nusa Lembongan - I Kadek Yoga Sucipta; Wayan Sri Maitri (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
Human resources are a key asset that determines the success of an organization or company. Optimal employee performance is a crucial indicator in achieving company goals. This study aims to determine the impact of leadership style, work motivation, and the work environment on employee performance at Naturale Villa Nusa Lembongan. The sampling technique used in this study was saturated sampling, with a sample size of 35 employees. Data were collected using documentation and questionnaires, and multiple linear regression analysis was performed using SPSS version 26. Based on the analysis, this study shows that leadership style has a positive and significant effect on employee performance at Naturale Villa Nusa Lembongan. This means that the better the leadership style implemented by the superior, the higher the employee's performance. Work motivation has a positive and significant effect on employee performance at Naturale Villa Nusa Lembongan. This means that the higher the employee's work motivation, the higher their performance. The work environment has a positive and significant effect on employee performance at Naturale Villa Nusa Lembongan. This means that the better and more conducive the work environment perceived by employees, the higher their performance